Islamic Republic of Mauritania : Transport Sector Overview - World Bank (Washington, DC, 2013)
The main Poverty Reduction Strategy Paper (PRSP) objectives for general transport policy are: a) lower costs, and ensure safe transport for passengers and goods; b) foster consistent national planning through multi-modal links between the country's major development centers; c) promote national integration, and linkages with the global economy; and, e) involve more private capital in financing the sector. The PRSP also includes specific objectives for transport modes, which are taken into account in this Economic and Sector Work (ESW). The purpose of this ESW is to provide a framework to help the Government analyze transport sector issues, and develop a transport sector strategy for the 2004-2009 period, and, identify issues and challenges that can be addressed through donor funded operations. This ESW focuses on road, air, and maritime transport, and analyzes strategic, and cross-cutting issues important to the sector as a whole. Recommendations include: corrections to the imbalance between investment and maintenance; improvement of the road maintenance financing mechanism; pursuit of a road investment program; strengthening the road management system; updating regulations to ensure effective liberalization of transport services; revision of the fiscal policy for the sector; improvement of the balance between supply and demand; and, identifying a mechanism for supporting the trucking industry.